Improving integrated skills through gamification in the EFL classroom. (2021)
The current social environment that surrounds the student’s perspectives and preferences causes an effect in the way to eventually interact with their learning processes. Gamification is a 21st century approach that proposes the use of the concepts of games to trigger motivation improvement, better performances, and better cognitive achievements, encouraging social interaction and independencies, and improving competitiveness between students through the learning process. Furthermore, the perspective of Role-Playing Games would be one of the many possible dynamics to adjust Gamification to an educational environment by structuring the proposal in disposal of the different integrated skills and enhancing their competitiveness through their learning process in an EFL classroom.